DINAMIKA SESAR CITARIK - Sidarto, Sidarto (Pusat Survei Geologi, 2008)
The NNE-SSW trending Citarik fault cut acrossWestern Jawa passing through Pelabuhan ratu, Bogor and Bekasi. At least, the fault has been active since Middle Miocene tectonic period. At that time, the Citarik fault was a transtensional fault, howeversince Plio-Pleistoceneuntil Recent, thisfaults has been developed as a left strike slip fault. The active Citarik Fault may generate earthquakes, and therefore it has to becarefully considered in planning Infrastructure developmentin Jabotabekand Pelabuhan ratu (the capital of Sukabumi Districtt and a tourist area). Keywords: Citarik fault, Middle Miocene - Recent, transtensional fault, left strike slip fault